The Political Stock Market in the German Kaiserreich — Do Markets Punish the Extension of the Suffrage to the Benefit of the Working Class? Evidence from Saxony. (27th November 2014) - Lehmann-Hasemeyer, Sibylle; Hauber, Philipp; Opitz, Alexander
Abstract : We approach the issue of the economic effects of democracy by examining which expectations investors held about the effect of democratization in the Kingdom of Saxony in 1896 and 1909. We do this by linking their investment behavior on the Berlin Stock Exchange to political events in Saxony. Here the electoral law was changed twice: In 1896 a very restrictive franchise was introduced, which was abolished in 1909 and replaced by a more democratic electoral law. Our study reveals that the Berlin Stock Exchange reacted to political changes and elections in Saxony. This is an important finding since historical research has claimed that the increased democratization in the German Kaiserreich measured in a larger participation of the population was not accompanied by a larger political influence of the parliaments. Furthermore we can show that for capital owners the possible negative effects seemed to outweigh possible positive effects of democratization. This is the first time that it has been possible to provide quantitative evidence for such antidemocratic sentiments.